MAKING THEM STRONG? VULNERABILITY, CAPABILITIES AND RESILIENCE IN POOR CHILDREN - Bagattini, Alexander; Gutwald, Rebecca (Gênero & Direito, 2016)
The main purpose of our paper consists in establishing the idea that the negative consequences that result from child poverty can be mitigated if the government and social workers promote the resilience of poor children. We use Amartya Sen’s capability approach as an evaluative framework to argue for this thesis. By distinguishing different sources of vulnerability we assume that children are inherently vulnerable, because they are dependent and in need of care. Poor children are, however, even more vulnerable in specific ways. Following Catriona MacKenzie, we call these vulnerabilities “pathogenetic”; they are caused by social arrangements like institutional settings. We claim that at least some some of those vulnerabilities can and should be diminished by promoting children’s resilience. We proceed in three steps. In the first part of the paper, we develop our concept of vulnerability and explain how child poverty renders children vulnerable to specific harms. Here we also introduce the capability approach by asking which capabilities children need for coping with this situation. In part two we argue that the concept of resilience helps us to understand why capabilities (and not resources or abilities) are relevant for coping with the adverse effects of child poverty. We claim that promoting the capabilities of children is a matter of justice, and that implementing resilience is, too. It is also highly important to see that promoting resilience is mainly a social matter, not a task the individual child has to fulfil on its own. Hence, we argue that children are entitled to gain those capabilities that promote their resilience against the adverse effects of poverty. In part three we discuss several difficulties of our account, such as the danger that children will be burdened with coping with the effects of poverty instead of society fighting poverty.